2013
DOI: 10.1001/jamadermatol.2013.4632
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fcγ Receptor Polymorphisms in the Response to Anti–Tumor Necrosis Factor Therapy in Psoriasis

Abstract: Preliminary results of this pilot study on the pharmacogenetics of FcγR and biological therapy in psoriasis suggest a role with clinical implications for FcγRIIA-H131R and FcγRIIIA-V158F polymorphisms in the outcome of anti-TNF treatment of psoriasis. These results might help dermatologists in guiding therapeutic decisions, especially in very severe cases where a quick response is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Recently, pharmacogenetic studies of FCGR2A and FCGR3A gene variants and anti-TNF therapy response have provided suggestive evidence for opposite genetic effects between rheumatoid arthritis and Crohn's disease, 33 rheumatoid arthritis and psoriatic arthritis 34 and even between rheumatoid arthritis and psoriasis. 20 Taken together, these results support the existence of different TNFrelated pathways and, consequently, different biologic mechanisms by which TNF blocking is an effective treatment.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Recently, pharmacogenetic studies of FCGR2A and FCGR3A gene variants and anti-TNF therapy response have provided suggestive evidence for opposite genetic effects between rheumatoid arthritis and Crohn's disease, 33 rheumatoid arthritis and psoriatic arthritis 34 and even between rheumatoid arthritis and psoriasis. 20 Taken together, these results support the existence of different TNFrelated pathways and, consequently, different biologic mechanisms by which TNF blocking is an effective treatment.…”
Section: Discussionmentioning
confidence: 63%
“…The PASI response measures the percentage of improvement in disease activity relative to a specified baseline. 20 The use of a relative score has the added advantage that it avoids any potential bias associated with different levels of disease activity at baseline. The association of the rs3794271 SNP genetic variation with the PASI response was performed using linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43] For all significant associations, except TLR9 (rs352139) and LY96 (rs11465996), similar tendencies were observed for ORs for each of the anti-TNF agents (data available on request). To our knowledge, this is one of the largest cohorts for evaluation of response in patients treated with ustekinumab 44,45 and the second largest for evaluation of anti-TNF; only a Canadian study (also involving treatment primarily for psoriatic arthritis) had more patients.…”
Section: Study Populationmentioning
confidence: 61%
“…Patients homozygous for high-ainity alleles of two variants FCGR2A-H131R (rs1801274) and FCGR3A-V158F (rs396991) had a higher chance of achieving PASI75 after 3 months of therapy [57]. FCGR3A rs396991 was also evaluated by Mendrinou et al who showed that T allele could be a marker of beter response to etanercept [58].…”
Section: Pharmacogenetics Of Anti-tnfα Treatmentmentioning
confidence: 99%